2019
DOI: 10.26508/lsa.201800215
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a constitutively active humanSTINGmutant in hematopoietic cells produces anIfnar1-dependent vasculopathy in mice

Abstract: STING-associated vasculopathy with onset in infancy (SAVI) is an autoinflammatory disorder characterized by blood vessel occlusions, acral necrosis, myositis, rashes, and pulmonary inflammation that are the result of activating mutations in the STimulator of Interferon Genes (STING). We generated a transgenic line that recapitulates many of the phenotypic aspects of SAVI by targeting the expression of the human STING-N154S–mutant protein to the murine hematopoietic compartment.hSTING-N154Smice demonstrated fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Collectively these findings suggest that the phenotype of murine SAVI is largely IFN-independent. In contrast, the SAVI disease pathology observed in mice expressing transgenic human STING N154S appeared to be highly dependent on Ifnar expression [158]. Of note, human STING N154S mice failed to develop any significant lung pathology [158], which is a hallmark clinical feature of SAVI patients and mice.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Collectively these findings suggest that the phenotype of murine SAVI is largely IFN-independent. In contrast, the SAVI disease pathology observed in mice expressing transgenic human STING N154S appeared to be highly dependent on Ifnar expression [158]. Of note, human STING N154S mice failed to develop any significant lung pathology [158], which is a hallmark clinical feature of SAVI patients and mice.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the SAVI disease pathology observed in mice expressing transgenic human STING N154S appeared to be highly dependent on Ifnar expression [158]. Of note, human STING N154S mice failed to develop any significant lung pathology [158], which is a hallmark clinical feature of SAVI patients and mice. Interestingly, T cells from N153S SAVI mice appear to undergo significant cell death, linked to ER stress and the unfolded protein response (UPR) [159].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hyperactivation of STING as a consequence of these gain-of-function mutations and subsequent type I IFN production then results in sterile inflammation, mainly affecting the skin and the lungs [7,69]. In opposition to AGS, despite severe systemic inflammation, neither gastrointestinal lesions have been described in the original publication, nor have gastrointestinal affections been evaluated and described in any mouse models investigating SAVI [7,[70][71][72][73].…”
Section: Origins Of Cgas/sting Activity and Type I Ifns In The Intestinementioning
confidence: 99%
“…Recent studies found that the abnormal activation of STING leads to immune dysfunction and induces autoimmune diseases such as Aicardi-Goutieres syndrome, systemic lupus erythematosus, and STING-associated vasculopathy with onset in infancy (SAVI), drawing attention to the need for the development of STING inhibitors. [129][130][131] Two nitrofuran derivatives, C-178 and C-176, covalently act on the predicted transmembrane cysteine residue Cys91, thus blocking activated STING by palmitoylation. The species-specificity of C-178 and C-176 indicated that the compounds were targeted to mouse STING (mmSTING) and not to human STING (hsSTING).…”
Section: Inhibitors Of Stingmentioning
confidence: 99%